The Role of Islam In the Formation of Malcolm X’s Identity and Thoughts - Jasmani, Nur Izzati (Al-Muqaddimah: Online Journal of Islamic History and Civilization, 2023)
This study analyses the role of Islam in the formation of Malcolm X’s identity and thoughts. Focusing on his moral foundation and evolving beliefs, particularly in theology and politics, this research seeks to elucidate the role of Islam in shaping Malcolm X’s worldview and serving as a moral foundation in his sentiments. The research methodology employed in this study is a qualitative approach with a historical research design. Data collection involves the use of documentation methods and the gathered data are analysed using historical analysis. As a result, the study findings reveal that despite challenging circumstances, Malcolm X successfully emerged from moral decay, discovering a renewed sense of purpose through Islam. Notably, Islam’s principles of justice and equality resonated with Malcolm X. The religion’s clear stance on racial matters captivated him, aligning with his pursuit of equality. In essence, Malcolm X’s comprehension of Islam significantly contributed to the evolution of his ideas concerning identity, racial dynamics and justice in the American context. The study emphasises how Islam became a transformative force in Malcolm X’s life, shaping his vision for a more equitable and just society.